pH effect on wettability of oil/brine/carbonate system: Implications for low salinity water flooding - Xie, Sam; Sari, A.; Pu, W.; Chen, Y.; Brady, P.; Al Maskari, N.; Saeedi, Ali (Elsevier, 2018)
© 2018 Elsevier B.V. Wettability of oil/brine/carbonate system is a critical parameter to govern subsurface multi-phase flow behaviour, thus remaining oil saturation and ultimate oil recovery in carbonate reservoirs. Despite the fact that salinity level, ionic strength, oil composition and rock chemistry (e.g., limestone and dolomite) have been extensively investigated, few work has been done regarding the effect of pH on oil/brine/rock interaction, thus wettability. We thereby measured contact angles at two different pH (pH = 3 and 8) in the presence of either 1 mol/L Na 2 SO 4 or 1 mol/L CaCl 2 using a crude oil with acid number of 1.7 and base number of 1.2 mg KOH/g. Moreover, we performed a geochemical modelling study in light of the diffuse double layer to understand how pH controls the number of surface species at interfaces of oil/brine and brine/carbonate. Our results show that pH scales with oil/brine/carbonate wettability, demonstrating that pH is one of the controlling factors to govern the system wettability. Further, our results suggest that pH (6.5–7.5) likely triggers an oil-wet system, which is favourable for low salinity water flooding, but pH < 5 usually exhibits a water-wet system, which explains why low salinity effect is not always observed in carbonate reservoirs. This also confirms that CO 2 flooding, carbonated water flooding, and CO 2 huff-and-puff EOR very likely renders a strongly water-wet system due to H + adsorption on the interface of oil/brine and brine/carbonate as a result of CO 2 dissolution.